2021
DOI: 10.3390/metabo11060404
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Course Comparison of Skeletal Muscle Metabolomic Alterations in Walker-256 Tumour-Bearing Rats at Different Stages of Life

Abstract: Cancer cachexia is a severe wasting condition that needs further study to find ways to minimise the effects of damage and poor prognosis. Skeletal muscle is the most impacted tissue in cancer cachexia; thus, elucidation of its metabolic alterations could provide a direct clue for biomarker research and be applied to detect this syndrome earlier. In addition, concerning the significant changes in the host metabolism across life, this study aimed to compare the metabolic muscle changes in cachectic tumour-bearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 72 publications
3
8
0
Order By: Relevance
“…We have previously reported dramatic muscle wasting of limb and trunk muscles in response to long-term CMV ( Ochala et al, 2011 ; Corpeno et al, 2014 ; Salah et al, 2016 ). In accordance with previous transcriptomic analyses, metabolite alterations were associated with an accelerated degradation of myofibrillar proteins in response to immobilization and CMV such as augmented levels of branch-chain amino acids (BCAAs; leucine, isoleucine, and valine) and their catabolic metabolites in both diaphragm and intercostals ( Figures 5A , 6 ), since myofibrillar proteins are composed of 18% BCAAs ( Baracos and Mackenzie, 2006 ; Chiocchetti et al, 2021 ). DMs involved in “Dipeptide” were significantly decreased, especially in the diaphragm ( Figures 5A , 7D ).…”
Section: Discussionsupporting
confidence: 89%
“…We have previously reported dramatic muscle wasting of limb and trunk muscles in response to long-term CMV ( Ochala et al, 2011 ; Corpeno et al, 2014 ; Salah et al, 2016 ). In accordance with previous transcriptomic analyses, metabolite alterations were associated with an accelerated degradation of myofibrillar proteins in response to immobilization and CMV such as augmented levels of branch-chain amino acids (BCAAs; leucine, isoleucine, and valine) and their catabolic metabolites in both diaphragm and intercostals ( Figures 5A , 6 ), since myofibrillar proteins are composed of 18% BCAAs ( Baracos and Mackenzie, 2006 ; Chiocchetti et al, 2021 ). DMs involved in “Dipeptide” were significantly decreased, especially in the diaphragm ( Figures 5A , 7D ).…”
Section: Discussionsupporting
confidence: 89%
“…These results were similar to previous studies using the same experimental model [26][27][28]. Of note, these alterations happened in both tumour-bearing groups but were more severe in WW animals, likely suggesting a higher spoliation in younger hosts, corroborating our previous report [17]. Although we did not find differences in relative liver weight in the present study, we found an altered liver metabolomic profile, gene and protein expressions imposed by the tumour growth, which were differentially affected by life stage in tumour-bearing animals.…”
Section: Discussionsupporting
confidence: 93%
“…Our previous 1 H-NMR-based study showed serum metabolite alterations associated with muscle metabolic pathways related to energy production and protein breakdown in Walker-256 tumourbearing animals [15,16]. We also found metabolic changes in skeletal muscle, showing altered metabolites mainly related to increased levels of amino acids and altered energetic metabolism, suggesting an expressive catabolic process and energy production in the youngest host, depicting differences between muscle responses depending on the host developmental stages [17].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…The metabolic alterations mostly focused in several metabolic pathways, including amino acid biosynthesis which was upregulated in the aging group and downregulated in the tumor groups (Viana et al, 2020). Recently, they also performed NMR-based metabolomic analysis on gastrocnemius derived from weanling and young adult rats, aiming to explore metabolic alterations in cachectic hosts during the whole lifespan (Chiocchetti et al, 2021). They indicated that the most significant variations of metabolites such as glutamate, glutamine, glycine, and methylhistidine, might be associated with the early muscle catabolism and declined energy generation in cachectic muscles.…”
Section: Metabolic Signatures and Metabolic Pathwaysmentioning
confidence: 99%